1966
DOI: 10.1073/pnas.55.1.170
|View full text |Cite
|
Sign up to set email alerts
|

ATP formation caused by acid-base transition of spinach chloroplasts.

Abstract: Previous workl-5 has shown the existence of a high-energy condition of isolated chloroplasts, caused by illumination in the absence of phosphate or ADP. This state is inferred from the ability to form ATP in the postillumination darkness. Accompanying the condition is an apparent uptake of hydrogen ions6z I together with an excretion of Mg++ or other cations.8 A feasible interpretation, stemming from the "chemi-osmotic" hypothesis for the mechanism of phosphorylation in double membrane containing organelles,9'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
138
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(143 citation statements)
references
References 12 publications
5
138
0
Order By: Relevance
“…Spinach chloroplast fragments with a high volume to surface ratio were prepared by osmotic shock as previously described [4] by washing whole chloroplasts in a medium containing impermeant osmotic supports such as 10 mM sodium succinate and 0.1 n-M tricine pH 8.0 or 10 mM sucrose containing 1 mM MgCl, and 0.1 mM sodium tricine at pH 8.0. The washed chloroplasts were resuspended in the above solutions for use in the experiments described herein.…”
Section: Methodsmentioning
confidence: 99%
“…Spinach chloroplast fragments with a high volume to surface ratio were prepared by osmotic shock as previously described [4] by washing whole chloroplasts in a medium containing impermeant osmotic supports such as 10 mM sodium succinate and 0.1 n-M tricine pH 8.0 or 10 mM sucrose containing 1 mM MgCl, and 0.1 mM sodium tricine at pH 8.0. The washed chloroplasts were resuspended in the above solutions for use in the experiments described herein.…”
Section: Methodsmentioning
confidence: 99%
“…This electrochemical potential difference of protons, ~x+. gives rise to a proton flux across the membra.ne, and the membrane-bound H +-ATPase can use the energy front this "down-hill" proton flux for synthesis of ATE ATP synthesis in chloroplasts can be driven by an artificially generated ApH (acid-base-transition [3]7 and dr/ (extental electric field [4] during the reaction time. Here, we measured the initial rate of" ATP synthesis with a rapid-mixing quenchedflow apparatus [5].…”
Section: Introductionmentioning
confidence: 99%
“…At about this time, Jagendorf and Uribe (1966) reported that chloroplasts could form ATP without illumination if they were incubated briefly in a low pH medium (acid) followed by quick addition of a base. The acid-base transition was believed to have created a proton concentration difference across the thylakoid membrane.…”
Section: Berger Mayne's Initial Research At the Kettering Laboratorymentioning
confidence: 99%